2020
DOI: 10.1177/0003134820964464
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Progression of Appendiceal Mucinous Neoplasm to Pseudomyxoma Peritonei

Abstract: Appendiceal mucinous neoplasm (AMN) can present with a spectrum of disease. Predicting factors in development of pseudomyxoma peritonei (PMP) from AMN could aid in management and treatment. The aim of this study was to determine factors predictive of PMP from AMN. This was a retrospective multicenter study of all patients diagnosed with AMN from 2006-2017. Diagnosis of PMP was compared by (1) patient demographics, (2) tumor characteristics, and (3) surgery. Secondary end points were disease-specific survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It was revealed that age, tumor rupture at presentation, tumor size, and CA19-9 levels might be associated with the progression of PMP. We found that tumor rupture was a risk factor leading to PMP in patients with AMN, which was supported by other studies ( 34 ) indicating tumor rupture at presentation was the only factor significantly associated with PMP. The follow-up data (median: 19 months, ranging from 2 to 47.5 months) showed no significant difference in the OS between patients with non-LAMN and LAMN, and between patients with PMP and without PMP.…”
Section: Discussionsupporting
confidence: 90%
“…It was revealed that age, tumor rupture at presentation, tumor size, and CA19-9 levels might be associated with the progression of PMP. We found that tumor rupture was a risk factor leading to PMP in patients with AMN, which was supported by other studies ( 34 ) indicating tumor rupture at presentation was the only factor significantly associated with PMP. The follow-up data (median: 19 months, ranging from 2 to 47.5 months) showed no significant difference in the OS between patients with non-LAMN and LAMN, and between patients with PMP and without PMP.…”
Section: Discussionsupporting
confidence: 90%
“…In most cases with suspected appendicular mucinous neoplasms, appendectomy is recommended, and in the worst-case scenario, cecectomy or ileocecectomy is performed to avoid the morbidity of a right hemicolectomy. This is usually sufficient for low-grade mucinous neoplasms, where the histopathological report will guide subsequent therapeutic decisions, with the need for right hemicolectomy in 20% of cases due to reports of high-grade neoplasms [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Although not all patients with NI-MAN rupture progress to PMP, macroscopic or microscopic dissemination of mucin to the peritoneum increases the risk of PMP recurrence. In a study by Sueda et al [ 24 ] in 136 patients with NI-MAN, tumor rupture on presentation was associated with the development of PMP. With the exception of patients with established peritoneal disease at the time of index surgery, 14% of patients with ruptured appendix subsequently developed PMP.…”
Section: Discussionmentioning
confidence: 99%